2013
DOI: 10.1007/s10549-013-2524-z
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative molecular analysis of total tumor load in sentinel lymph node: a new predictor of axillary status in early breast cancer patients

Abstract: TTL by OSNA is a newly standardized and automated tool that predicts axillary node status better and independently of the number of affected SLNs and the type of surgery. This value can then help clinicians to personalize surgical treatment. Prospective studies will be carried out to determine the clinical impact of this variable in the management of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
79
3
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 29 publications
5
79
3
6
Order By: Relevance
“…In this study, univariate analysis showed that tumor size, number of SLN macrometastases and CK19 mRNA copies (TTL) determined by OSNA assay were significantly associated with non-SLN metastases. These results are in line with other studies [9,10]. However, in multivariate analysis, TTL was the only variable with a significant association that could be used intraoperatively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, univariate analysis showed that tumor size, number of SLN macrometastases and CK19 mRNA copies (TTL) determined by OSNA assay were significantly associated with non-SLN metastases. These results are in line with other studies [9,10]. However, in multivariate analysis, TTL was the only variable with a significant association that could be used intraoperatively.…”
Section: Discussionsupporting
confidence: 92%
“…Reportedly, TTL can be used as a predictor for non-SLN metastases [9,10]. We studied the prediction model with TTL using the ROC curve, which had good discrimination acuity (AUC ¼ 0.805) in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this new strategy, an ALD would not be performed in women with T1 tumors of luminal subtype A, women aged more than 50 years, and in cases of conservative breast surgery in which the total tumor burden, according to a 1-step nucleic acid amplification (OSNA) of the SLN, 10 was less than 15,000 copies. 11 The reasoned justification was that if the patient met the criteria for not performing a lymphadenectomy, it would be pointless to perform an intraoperative study of the SLN during surgery, and therefore, it would make more sense to perform the study postoperatively, thus saving surgical time. However, in those patients with clinical criteria for performing an ALD, our protocol includes the recommendation to perform the SLNB intraoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…Se define la CTT como la suma del número de copias de ARNm de la citoqueratina 19 (ARNm-CK-19) de todos los GC y ha sido identificada por algunos autores como el factor independiente predictivo de metástasis en los ganglios axilares no centinela de mayor potencia 18,19 .…”
Section: Introductionunclassified